Deep learning for domain-specific action recognition in tennis - Mora, S. V.; Knottenbelt, W. J. (IEEE/CVF Conference on Computer Vision and Pattern Recognition, 2017)
Recent progress in sports analytics has been driven by the availability of spatio-temporal and high level data. Video-based action recognition in sports can significantly contribute to these advances. Good progress has been made in the field of action recognition but its application to sports mainly focuses in detecting which sport is being played. In order for action recognition to be useful in sports analytics a finer-grained action classification is needed. For this reason we focus on the fine-grained action recognition in tennis and explore the capabilities of deep neural networks for this task. In our model, videos are represented as sequences of features, extracted using the well-known Inception neural network, trained on an independent dataset. Then a 3-layered LSTM network is trained for the classification. Our main contribution is the proposed neural network architecture that achieves competitive results in the challenging THETIS dataset, comprising videos of tennis actions.